(untitled) (Modern education and development, 2025)
This study investigates the lexical-semantic features of tourism terms in English and Uzbek languages, aiming to identify similarities and differences between the two languages in the context of tourism. A corpus of tourism-related texts in English and Uzbek is analyzed, and the semantic fields, conceptual structures, and cultural connotations of tourism terms are examined. The findings contribute to cross-linguistic studies and enhance our understanding of the linguistic aspects of tourism in these languages.